Women's financial well‐being: A systematic literature review and directions for future research. (19th April 2021) - Gonçalves, Virginia Nicolau; Ponchio, Mateus Canniatti; Basílio, Roberta Gabriela
Abstract: The study of financial well‐being has gained attention in recent years and a number of scholarly articles have pointed to gender‐related differences and their antecedents and consequents. The continuous growth of scholarly literature on women's financial well‐being and its dispersion impose difficulties for researchers to comprehensively assess the state of knowledge on the topic. In this context, the objectives of this research are to conduct a systematic literature review of women's financial well‐being and to propose directions for future research. This study comprises a review of 130 articles published in peer‐reviewed journals over the period 1990–2020. Bibliometric analysis was used to identify the year of publication and the countries surveyed, journal of publication, methodologies, concepts, measures and theoretical frameworks utilized; subsequent content analysis allowed us to summarize the main findings. We organized the identified antecedents of women's financial well‐being into three categories: individual, household and community and societal level elements. The elements that constitute these categories are discussed and our findings point to important gender‐related differences. Based on the identified literature gaps, directions for future research are proposed. The theoretical contribution of this study lies in delivering a comprehensive overview of available evidence on women's financial well‐being. Its practical and societal implications include the provision of knowledge that may allow better targeting of financial education programmes, economic empowerment interventions and public policies, which may help reduce the financial well‐being gender gap.